Race and racism in international relations : confronting the global colour line - Anievas, Alexander; Manchanda, Nivi; Shilliam, Robbie, 1969- (Milton Park, Abingdon, Oxon: Routledge, 2015)
'International Relations, as a discipline, does not grant race and racism explanatory agency in its conventional analyses, despite such issues being integral to the birth of the discipline. Race and Racism in International Relations seeks to remedy this oversight by acting as a catalyst for remembering, exposing and critically re-articulating the central importance of race and racism in International Relations'--
Confronting the Global Colour Line : an Introduction / Alexander Anievas, Nivi Manchanda and Robbie Shilliam -- Hidden in Plain Sight : Racism in International Relations Theory / Errol Henderson -- Through, Against, and Beyond the Racial State : The Transnational Stratum of Race / Debra Thompson -- Good Governance and State Failure : the Pseudo-Science of Statesmen in Our Times / Branwen Gruffydd-Jones -- Re-Embedding the Global Colour Line within Post-1945 International Theory / John M. Hobson -- Against Race Taboos : The Global Colour Line in Philosophical Discourse / Srdjan Vucetic -- Colonial Violence : Race and Gender on the Sugar Plantations of British Guiana / Randolph B. Persaud -- A Postcolonial Racial/Spatial Order : Gandhi, Ambedkar and the Construction of the International / Sankaran Krishna -- The Cold War, American Anticommunism and the Global Colour Line / Richard Seymour -- Race, Racialisation and Rivalry in the International Legal Order / Robert Knox -- What Would It Mean to Transform International Relations? / David Roediger -- Unwriting and Unwhitening the World / Charles W. Mills.
Includes bibliographical references and index.
Keywords: International relations -- Social aspects; Racism -- Political aspects; Race -- Political aspects